2000
DOI: 10.1111/j.1532-5415.2000.tb03869.x
|View full text |Cite
|
Sign up to set email alerts
|

Tube Feeding in Nursing Home Residents with Severe and Irreversible Cognitive Impairment

Abstract: Clinical variables including swallowing problems, stroke, and absence of dementia were strongly associated with the use of feeding tubes in this cross-sectional, population-based study. In addition, urban location of nursing home and non-white race were significantly associated with feeding tubes. These findings suggest that feeding tube decisions are strongly influenced by nonclinical factors and invite further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
67
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 50 publications
8
67
1
Order By: Relevance
“…Part III presented preference, physician personal, patient, and situational factors (associated with tube feeding in prior literature) [17][18][19][20] and asked the physician to rate the importance of each factor in their decision to withhold or withdraw tube feeding on a three-point Likert scale.…”
Section: Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…Part III presented preference, physician personal, patient, and situational factors (associated with tube feeding in prior literature) [17][18][19][20] and asked the physician to rate the importance of each factor in their decision to withhold or withdraw tube feeding on a three-point Likert scale.…”
Section: Measurementmentioning
confidence: 99%
“…10,14,15 Physician ethnicity was associated with tube feeding decisions, 16 and patient and institutional factors associated with tube feeding in nursing home patients have been identified in previous observational studies. [17][18][19][20] However, the physicians' perception of the importance of these factors in tube-feeding decision-making has not been examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aronheim et al (2001) found wide regional variation in the US in the use of tube feeding in residents with severe cognitive impairments, with a rate of 7.5% in the state of Maine and 40.1% in Mississippi. Within the state of Kansas, Gessert et al (2000) found that certain characteristics in the population (n = 4997) were more likely to predict tube use; odds ratios (ORs) showed that swallowing problems (OR 5.4), urban location (OR 2.9), non-white race (OR 2.7), stroke (OR 2.5) and absence of dementia (OR 2.5) were predictive of tube use. Of those dependent in all activities of daily living, 74% used tubes and 80.1% of those with either chewing or swallowing problems had tubes.…”
Section: Use Of Tube Feedingmentioning
confidence: 98%
“…For example, non-White residents are significantly more likely to be tube fed than White NH residents (Mitchell, Teno, & Roy, 2003). NHs with full-time speech therapists on staff, fewer nursing assistants, and located in an urban setting are associated with higher rates (Gessert, Mosier, Brown, & Frey, 2000). Research also suggests financial incentives exist for gastroenterologists, hospitals, and NHs .…”
mentioning
confidence: 99%